Analisis Multimodal pada Sampul Majalah Tempo Pilpres 2024: Kajian Semiotika Sosial - Isma Farikha Latifatun Nuzulia (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to analyze the newspaper coverage of the presidential election 2024 because this issue was a controversial phenomenon and has many perspectives for the community. The method used was descriptive qualitative since it describes a social phenomenon with the verb and visual meaning. The source was obtained from the Tempo website with politically based, namely https://majalah.tempo.co , and the data was an optical element and languages such as phrases and sentences. After analysis, it was found that all data is based on the idea of the 2024 presidential election in a narrative representational form because the visual maker presents a story from the elements that appear. In the interactive meaning, the visual maker uses statements and interrogative sentences to interact with the reader and employs an eye-high view visual form parallel to the reader's eye line. Then the textual meaning and composition are presented in the form of all verbs as a linguistic expression for the visual maker and certain elements that want to highlight, such as the color red, President Jokowi, billboards on the street, and ministers.